Single-Cell Analysis of Target Antigens of CAR-T Reveals a Potential Landscape of “On-Target, Off-Tumor Toxicity” - Zhang, Yinyin; Li, Yingmei; Cao, Weijie; Wang, Fang; Xie, Xinsheng; Li, Yadan; Wang, Xiaoyi; Guo, Rong; Jiang, Zhongxing; Guo, Rongqun (Frontiers in Immunology, 2021)
Cellular immunotherapy represented by CD19-directed chimeric antigen receptor T (CAR-T) cells has achieved great success in recent years. An increasing number of CAR-T therapies are being developed for cancer treatment, but the frequent and varied adverse events, such as “on-target, off-tumor toxicity”, limit CAR-T application. Here, we identify the target antigen expression patterns of CAR therapies in 18 tissues and organs (peripheral blood mononuclear cells, bone marrow, lymph nodes, spleen, heart, ascending aortic tissue, trachea, lung, skin, kidney, bladder, esophagus, stomach, small intestine, rectum, liver, common bile duct, and pancreas) from healthy human samples. The atlas determines target antigens expressed on some normal cell types, which facilitates elucidating the cause of “on-target, off-tumor toxicity” in special tissues and organs by targeting some antigens, but not others. Moreover, we describe the target antigen expression patterns of B-lineage-derived malignant cells, acute myeloid leukemia (AML), and solid tumors. Overall, the present study indicates the pathogenesis of “on-target, off-tumor toxicity” during CAR therapies and provides guidance on taking preventive measures during CAR treatment.